Lelaki Tua dan Laut Karya Ernest Hemingway (Sebuah Ulasan) - Mirya Anggrahini Nimpuno (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
Novel Lelaki Tuadan Laut by Ernest Hemingway contains many of the themes that preoccupied Hemingway as a writer and as a man. The routines of life in a Cuban fishing village are evoked in the opening pages with a characteristic economy of language. The stripped-down  existence of the fisherman Santiago is crafted in a spare, elemental style that is as eloquently dismissive as a shrug of the old man’s powerful shoulders.Hemingway was famously fascinated with ideas of men proving their worth by facing and overcoming the challenges nature. Through his struggle, Santiago demonstrated the ability of the human spirit to endure hardship and suffering in order to win. It is also his deep love and knowledge of the sea, in its impassive cruelty and beneficence, that allows him to prevail. The essential physicality of the story – the smells of tar and salt and fish blood, the cramp and nausea and blind exhaustion of the old man, the terrifying death spasm of the great fish – is set against he ethereal qualities of dazzling light and water, isolation, and the swelling motion of the sea. And through it all narrative is constantly tugging, unreeling a little more, and then pulling again, all in tandem with the old man’s struggle.Structural analysis aims to describe (1) elements, characters, settings, and perspectives in the novel Old Man and The Sea, (2) the interrelationships between intrinsic elements in the form of themes, plot, background, character, characterization and perpective in the novel Old Man and The Sea by Ernest Hemingway.